STRATEGI PENGEMBANGAN AGROINDUSTRI GULA AREN DI DESA TONDEI 1 - Novita ., Wongkar; Joachim N. K. Dumais; Theodora M. Katiandagho (Sam Ratulangi University, 2017)
The purpose of this research is to identify the right development strategy in Tondei Village 1, Sub-district of West Motoling, South Minahasa Regency. The research was conducted in September until November 2017, using primary and secondary data with 10 respondents. Data primary collection through interviews using questionnaires. Secondary data collected from the office of Tondei 1 Village. Research data in the analysis using SWOT analysis. The result of the research shows that the result of internal strategic factor analysis shows that the total score of internal analysis result is 3.16 indicating that it is in a